Effect of Coarse Aggregate Gradation on the Strength Properties of Bagasse Ash Concrete - Malak, Irshad Ali; Narwani, Tulsi Das; Memon, Bashir Ahmed; Wato, Jan Muhammad; Jokhio, Naeem Ahmed; Mallah, Sajid Ali (Engineering, Technology & Applied Science Research, 2023)
This study investigated the coarse aggregate grades and the use of sugarcane bagasse ash as a replacement for cement to examine their effect on concrete strength. Ten concrete mixes were prepared in two groups using a 1:2:4 mix ratio and a 0.48 water-to-binder ratio. Sugarcane bagasse ash was used in 0 and 10% dosages by weight of cement. Five grades of aggregates were used: 4.75-7, 7-10, 10-13, 13-20, and 4.75-20mm. Six 6"/12" concrete cylinders were prepared for each group and cured for 28 days to test their compressive and split tensile strengths. The results showed that bagasse ash caused a reduction in strength properties in both well- and specific-graded concrete. It was also observed that 10-13mm aggregate concrete with and without bagasse ash had more strength than the respective well-graded. Although a minimum decrease in strength was observed, a 10% dosage of sugarcane bagasse ash was optimal to save cement content in both specific and well-graded aggregate concrete. This study provides a new framework for using graded coarse aggregates and replacing cement with bagasse ash.